2015
DOI: 10.3906/vet-1401-26
|View full text |Cite
|
Sign up to set email alerts
|

Determination of nutrient content and digestibility characteristics ofPrangos ferulacea (L.) on grazing lands of Eastern Anatolia

Abstract: The aim of this study was to compare nutrient content, and in situ protein and organic matter degradation kinetics of Prangos ferulacea (L.) (locally called helis), a naturally growing plant on the top of Mount Artos, with those of alfalfa. P. ferulacea plants used in the study were collected from three different parts of Mount Artos in Van Province over two years. While organic matter content and in vitro organic matter digestibility of P. ferulacea were significantly higher, neutral detergent fiber, acid det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Indeed, especially the increase in ADF content adversely affects digestibility. Aldemir et al (2015) and Coşkun et al (2004) suggested that the in vitro dry matter digestibility of Prangos ferulacea hay is 79.15 and 80.60%, respectively. These values are higher than the values found H hay in this study, while Shawrang et al (2013) are similar to the effective dry matter degradability value found for Prangos ferulacea.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, especially the increase in ADF content adversely affects digestibility. Aldemir et al (2015) and Coşkun et al (2004) suggested that the in vitro dry matter digestibility of Prangos ferulacea hay is 79.15 and 80.60%, respectively. These values are higher than the values found H hay in this study, while Shawrang et al (2013) are similar to the effective dry matter degradability value found for Prangos ferulacea.…”
Section: Discussionmentioning
confidence: 99%